Analisis Kebijakan Dinas Perhubungan Kota Bandar Lampung Dalam Mengatasi Kemacetan Lalu Lintas Melalui Operasionalisasi Bus Rapid Transit (Studi Di Kota Bandar Lampung) - Agus Iskandar (Law Faculty of Universitas Bandar Lampung, 2014)
Policy in traffic congestion by Government of Bandar Lampung directed to create good traffic order for the present and for the future. Problems of this research are: (1) What is the Department of Transportation policy of Bandar Lampung in addressing traffic congestion through the operationalization of Bus Rapid Transit? (2) What are the factors supporting and inhibiting Policy Bandar Lampung Transportation Agency in addressing traffic congestion through the operationalization of Bus Rapid Transit? This research approach is normative and empirical jurisdiction. Data was collected through library research and field study. The data was then analyzed to obtain qualitative researchconclusions. The results and discussion indicate: (1) Bandar Lampung city government policy in addressing traffic congestion through operationalization Bus Rapid Transit (BRT) is a policy that is both urgent and requires settlement in a short time , because congestion has become a problem that needs to be as soon as possible addressed. (2) The factors that support the policy of Bandar Lampung transportation agencies in addressing traffic congestion through the operationalization of Bus Rapid Transit is a legal umbrella operation of BRT, the BRT implementation and operationalization of the expectations of the people in town that mass transportation